The Effectiveness of Phonemic and Phonological Awareness Program To Improve Reading Performance of First Grade Basic Education Students in Oman - Sahar El Shorbagi; Rashid Al Mehrizi; Ali Al Zamli; Amal Al Kayoumi; Raya Al Munthiri; Thuwyba Al Barwani; Yusra Al Sinani (Sultan Qaboos University, 2017)
The aim of the study was to investigate the effect of a phonemic and phonological awareness program, on the Arabic reading performance of first grade basic education students in Oman. To achieve this aim, a quasi-experimental research design was adopted. An Arabic phonemic and phonological awareness test was designed together with training program for Arabic teachers. A sample of 205 students was selected from 4 schools and divided into two groups. The experiment was conducted in 10 weeks during which teachers taught using the program. A post-test was administered after the intervention and then the students were tested for the third time after six months to determine the delayed effect. Results showed that there were significant differences in the mean of the test scores between the control and the experimental groups in favor of the experimental group. Similarly, significant differences were indicated in the mean of the test scores among the experimental group between the pre and the post-test. On the other hand, no significant differences were noted between male and female students. Results also showed significant differences in the mean of the test scores among the experimental group in the third testing which was intended to measure the delayed effect.